2022
DOI: 10.1038/s41589-022-01024-4
|View full text |Cite
|
Sign up to set email alerts
|

PRMT inhibition induces a viral mimicry response in triple-negative breast cancer

Abstract: Triple-negative breast cancer (TNBC) is the most aggressive breast cancer subtype with the worst prognosis and few effective therapies. Here we identified MS023, an inhibitor of type I protein arginine methyltransferases (PRMTs), which has antitumor growth activity in TNBC. Pathway analysis of TNBC cell lines indicates that the activation of interferon responses before and after MS023 treatment is a functional biomarker and determinant of response, and these observations extend to a panel of human-derived orga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 51 publications
5
44
0
Order By: Relevance
“…Indeed, a viral mimicry response can be induced when using epigenetic inhibitors (histone methyltransferase EZH2 and PRMT1 inhibitors) that induce the expression of transposable element-derived double-stranded RNA. Such a response is able to activate an interferon response resulting in a potent antitumour effect [ 83 ]. Furthermore, a study has recently linked H3K4me3 (trimethylation of histone H3 at lysine 4) and H3K27me3 (trimethylation of histone H3 at lysine 27) to the persister cell population expression program in TNBC tumours.…”
Section: Novel Therapeutic Approaches For Tnbcmentioning
confidence: 99%
“…Indeed, a viral mimicry response can be induced when using epigenetic inhibitors (histone methyltransferase EZH2 and PRMT1 inhibitors) that induce the expression of transposable element-derived double-stranded RNA. Such a response is able to activate an interferon response resulting in a potent antitumour effect [ 83 ]. Furthermore, a study has recently linked H3K4me3 (trimethylation of histone H3 at lysine 4) and H3K27me3 (trimethylation of histone H3 at lysine 27) to the persister cell population expression program in TNBC tumours.…”
Section: Novel Therapeutic Approaches For Tnbcmentioning
confidence: 99%
“…Finally, it is important to note that TEs are not necessarily transcribed in an autonomous fashion, and a large fraction are found in introns. Moreover, de novo integration of TEs into exons or alternative splicing events allowing readthrough of intronic TEs (Wu et al, 2022) can generate fusion proteins that could serve as targetable antigens. Overall, TEs represent a specific source of immunogenic tumor antigens that can be recognized by T cells and induce a functional response (Laumont et al, 2018;Saini et al, 2020;Ehx et al, 2021) (Griffin et al, 2021).…”
Section: Te-derived Antigens Provide Shared Targets For Adaptive Resp...mentioning
confidence: 99%
“…Zhang et al demonstrated that inhibition of CDK9 led to the dephosphorylation of BRG1, a regulator of heterochromatin, and resulted in increased global gene expression, including expression of ERVs and IFN-I-associated signature (Zhang et al, 2018). Further, Wu et al demonstrated that inhibition of type I PRMTs in triple-negative breast cancer cell lines triggered aberrant splicing events, including the retention of introns containing IR-Alus that can form dsRNA, contributing to the induction of an IFN-I response (Wu et al, 2022). This work (Choi et al, 2021).…”
Section: Mediating Te Expressionmentioning
confidence: 99%
See 2 more Smart Citations